A Study of Oceanographic Conditions During the Tropical Cyclone Anggrek in the Coastal Area of Bengkulu - Rozylla Agustina; Supiyati Supiyati; Septi Johan; Siti Hairunnisa Norfahmi (Lambung Mangkurat University Press, 2026)
This research has not been discussed previously, especially in the waters of Bengkulu, which has a strategic position in relation to the formation and movement of tropical cyclones in the eastern Indian Ocean. The lack of research in this region has resulted in limited information on the direct impact of cyclones on oceanographic parameters. This study aims to identify the impact of tropical cyclone Anggrek on oceanographic parameters in Bengkulu waters during and after the occurrence of tropical cyclone Anggrek. This study is limited to the waters of Bengkulu with a focus on the period from January 15 to February 13, 2024. Reanalysis data from the Marine Copernicus numerical model was used and analyzed temporally with a quantitative descriptive approach, followed by a t-test: Paired Two Sample for Means. The results of the oceanographic parameter analysis showed significant changes due to the influence of Tropical Cyclone Anggrek in the waters of Bengkulu. Based on the results of the paired t-test, all main parameters showed significant differences between normal conditions and cyclone conditions. Sea surface temperature decreased during the cyclone due to vertical mixing processes, then increased again after the cyclone moved away. Salinity values also showed significant differences. Wave height and current velocity experienced noticeable fluctuations, and wind speed conditions during Tropical Cyclone Anggrek generally increased. The results of this study provide updates to BMKG predictions and support the strengthening of early warning systems in the western coastal region of Sumatra, particularly in the waters of Bengkulu, by understanding changes in sea and atmospheric conditions after the cyclone.